Perancangan Virtual Tour Agrowisata IBRU-Q Sebagai Media Informasi dan Promosi Online Desa Ibru - Ambarwati, Diah; Agustin, Imelda; Kuswanto, Hasby; Arsa, Daniel (Green Publisher Indonesia, 2024)
Ibru Village has significant potential in tourism and creative economy but lacks optimal utilization of information technology for promotion and dissemination of its potential. Most promotional efforts still rely on traditional methods with limited reach. This study aims to design a virtual tour system, Virtual Tour IBRU-Q, to serve as an interactive and modern promotional medium for Desa Ibru's agrotourism. Using the Multimedia Development Life Cycle (MDLC) method, the research focuses on the concept and design phases. The concept phase involves creating a research plan to address the issues and goals, while the design phase includes structuring the program architecture, user interface, and system flow using a procedural design approach. The resulting system integrates 360° virtual reality visuals, enabling users to explore Desa Ibru’s agrotourism virtually.